Model Tata Kelola TI Berbasis COBIT 2019 untuk Mendukung Transformasi Digital Koperasi (Studi kasus : KSPPS TAMZIS BINA UTAMA) - Iqbal Shobirin; Alfa Hendi Muhammad (G-Tech: Jurnal Teknologi Terapan, 2024)
Cooperative digitalization makes it transparent, accountable, easy, and fast, allowing cooperatives to address socio-economic needs effectively. The case study of KSPPS TAMZIS shows that IT governance is necessary to ensure that the use of cooperative technology can optimally support organizational goals. The COBIT 2019 framework was used in this research. The research method, Governance System Design Workflow, involves understanding objectives, strategies, determining the initial scope of the management system, refining the scope of the governance system, and producing conclusions for the governance system design. The mapping results show that the three priority domains are APO09 (Managed Service Agreements), BAI10 (Managed Configuration), and DSS01 (Managed Operations). When evaluating the process capability level, these three domains are at level 1, with the target set at level 4. There is a significant gap. Recommendations for improving IT governance operations are provided for each domain, with the priority for improvement on BAI10 to build a solid configuration management foundation, strengthening IT operational processes through DSS01, and improving user satisfaction by focusing on IT services through APO09.